A Study on Weak-Form of Market Efficiency in Selected Asian Stock Markets - Ryaly, Venkata Rajasekhar; Kiran Kumar, R. S. R. K.; Urlankula, Bhargava (Indian Journal of Finance, 2014)
Efficiency of financial markets is one of the key elements indicating the performance of financial markets and the economy. In efficient markets, all transactions are done with the help of new information available about the economy, industries, and companies. Stock price movements are completely random, and are highly based on current information. The historical sequence of the prices will not provide any platform/base for the future. There might be no use of studying historical data of price changes to gain abnormal returns. The main aim of the present study was to investigate the behavior of the daily stock returns in five Asian countries, namely India, South Korea, Singapore, Hong Kong, and Japan. We employed both parametric and non-parametric tests to check the RWH (random walk hypothesis) to know the weak form of efficiency in the Asian stock markets. A common data set for all countries covering the time period from July 1997 to November 2013 was considered for the study. The results provided reasonable evidence to prove the existence of weak form of market efficiency in the selected Asian stock markets.